Fabrication of Multi-Responsive Bioactive Nanocapsules through Orthogonal Self-Assembly() - Yeh, Yi-Cheun (2014)
Multifunctional self-assembled systems present platforms for fundamental research and practical applications, providing tunability of structure, functionality and stimuli response. Pragmatic structures for biological applications have multiple design requirements, including control of size, stability and environmental response. Here we present the fabrication of multifunctional nanoparticle-stabilized capsules (NPSCs) using a set of orthogonal supramolecular interactions. In these capsules, fluorescent proteins are attached to quantum dots through polyhistidine coordination. These anionic assemblies interact laterally with cationic gold nanoparticles that are anchored to the fatty acid core through guanidinium-carboxylate interactions. The lipophilic core then provides a reservoir for hydrophobic endosome-disrupting agents, generating a system featuring stimuli-responsive payload release into the cytosol with fluorescent monitoring.